Efficacy of individualized orelabrutinib-based regimens in relapsed or refractory central nervous system lymphoma - Wu, Yuchen; Sun, Xuefei; Lv, Liwei; Cui, Qu; Qian, Jun; Xing, Ruixian; Bai, Xueyan; Chen, Yuedan; Liu, Qing; Lai, Wenyuan; Gao, Chunji; Sun, Shengjun; et al. (Frontiers in Neurology, 2025)
BackgroundRelapsed or refractory central nervous system lymphoma (rrCNSL) lacks established preferred treatment and carries an inferior prognosis. Bruton’s tyrosine kinase inhibitor (BTKi) showed promising effectiveness. Orelabrutinib is a second-generation BTKi with a high concentration in cerebrospinal fluid.MethodsIn this retrospective analysis, the outcomes of 37 relapsed or refractory central nervous system diffuse large B-cell lymphoma patients who received orelabrutinib, high-dose methotrexate, ifosfamide, etoposide, and dexamethasone (Ore-MIED) or orelabrutinib, high-dose methotrexate, temozolomide and dexamethasone (Ore-MTD) were evaluated.ResultsOf the 37 patients included, 11 received Ore-MTD, and 26 received the Ore-MIED regimen. The overall response rate in our cohort was 89.2%, with complete remission achieved in 51.4% of patients and partial remission in 37.8% of patients. The median progression-free survival was observed to be 7.0 months. No statistically significant difference was found in the median progression-free survival between patients receiving different treatment regimens (5.0 months for Ore-MTD versus 13.0 months for Ore-MIED; p = 0.29). Moreover, the median overall survival has not been reached in this cohort, indicating a promising outcome despite the aggressive nature of the disease.ConclusionOur study confirms the effectiveness and safety of Ore-MIED/Ore-MTD in rrCNSL patients, even in those with previous exposure to multiple lines of treatment.